Farm size, irrigation practices, & on-farm irrigation efficiency in New Mexico's Elephant Butte Irrigation District - Skaggs, Rhonda, author; Samani, Zohrab, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Relationships between farm size, irrigation practices, and on-farm irrigation efficiency in the Elephant Butte Irrigation District, New Mexico, U.S.A. are explored using water delivery data supplied by the District. The study area is experiencing rapid population growth, development, and competition for existing water supplies. Analysis of pecan and alfalfa water delivery data, fieldwork, and interviews with irrigators found extremely long irrigation durations, inefficient irrigation practices, inadequate on-farm infrastructure, and little interest in making improvements to the current irrigation system or methods on the smallest farms. These findings are attributed to the nature of residential, lifestyle, or retirement agriculture. Irrigation practices on large farms are notably different from small farms: irrigation durations are shorter, less water is applied, producers are commercially oriented, and have high levels of on-farm efficiency. Many small producers appear to view irrigation as a consumptive, recreational, social, or lifestyle activity, rather than an income generating pursuit. Small farm operators are likely to show limited interest in improving on-farm irrigation infrastructure, adopting management intensive irrigation technologies or practices, or making significant irrigation investments. Easement and common property disputes over ditch maintenance between owners of small parcels also create disincentives for infrastructure improvements.
Elephant Butte Irrigation District
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."